The changes in multi-scale structure and properties of wheat starch after interaction with oligosaccharides of different polymerization degrees under different freeze-thaw cycles - Juanjuan Guo; Zengming Huang; Peilin Chen; Xiantong Wu; Xu Lu (Food Chemistry: X)
This study investigated the effects of three oligosaccharides, stachyose (STA), raffinose (RAF), and sucrose (SUC), all at 16 % w/w, on the physicochemical properties of wheat starch subjected to multiple freeze-thaw (FT) cycles. The findings revealed that all three oligosaccharides reduced starch particle size and mitigated the degradation of endogenous nutrients, such as proteins and lipids, typically induced by repeated FT treatments. Additionally, the oligosaccharides decreased the content of amylose, crystallinity and short-range molecular order of starch, as well as the gelatinization enthalpy (ΔH) and rapidly digestible starch. They also suppressed granule swelling, leading to reductions in peak, breakdown, and setback viscosities, thereby enhancing the shear resistance of the starch paste. Among the tested oligosaccharides, SUC was the most effective in preserving starch integrity and nutrient content, whereas STA had a greater capacity to reduce crystallinity and stabilize viscosity parameters. These results provide a theoretical foundation for optimizing the use of oligosaccharides in frozen wheat starch-based food products.